Preparation method for preparing high-compaction lithium iron phosphate positive electrode material by utilizing double-iron-source composite grade matching and high-compaction lithium iron phosphate positive electrode material

By controlling the pH of the iron phosphate slurry, different iron sources are prepared and lithium iron phosphate are synthesized, combined with high and low temperature calcination, the problems of low energy density and high cost of lithium iron phosphate are solved, and the effects of high compaction density and low cost are achieved.

CN120117581AActive Publication Date: 2025-06-10HUBEI XINGFA CHEM GRP CO LTD

Patent Information

Application Number
CN202510540489.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-06-10
Estimated Expiration
2045-04-27

AI Technical Summary

Technical Problem

The energy density of existing lithium iron phosphate is low, and the carbon source is required for iron reduction during the synthesis of traditional high-temperature solid-phase method, which increases the cost.

Method used

By controlling the pH of the iron phosphate slurry section, different iron sources are prepared, and lithium iron phosphate is synthesized using two paths in the same reaction vessel, combined with high and low temperature calcination, the purpose of grading of large and small particles is achieved.

Benefits of technology

It improves the compaction density of lithium iron phosphate, reduces costs, and has a simple process, green and environmentally friendly materials, and is easy to develop in industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120117581A_ABST
    Figure CN120117581A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method for preparing a high-compaction lithium iron phosphate positive electrode material by utilizing double-iron-source composite grade matching. The preparation method comprises the following steps: adding ferrous sulfate and phosphoric acid into pure water, and fully mixing to obtain a solution; dividing the solution into a solution A and a solution B; adding a certain amount of a metal doping source material, an oxidizing agent and phosphoric acid into the solution A, and controlling the pH to be 1-3 to obtain iron phosphate; adding a certain amount of metal doped source material and ammonia water into the solution B, and controlling the pH to be 5-6 to obtain ferrous phosphate; the preparation method comprises the following steps: respectively sanding and spraying iron phosphate and ferrous phosphate with a lithium source, a carbon source and pure water according to a molar ratio to obtain a lithium iron phosphate yellow material A and a lithium iron phosphate yellow material B; calcining the yellow material A in a furnace to obtain a precursor A, calcining the yellow material B in the furnace to obtain a precursor B, mixing the precursor A and the precursor B according to a certain mass ratio, and calcining to obtain a finished product. The method is simple in technological process, can be combined with actual production, and is very effective for improving the compaction density and the electrical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium ion battery positive electrode material and a preparation method thereof in the field of electrochemical energy storage, and in particular to a preparation method of a high-density lithium iron phosphate positive electrode material prepared by using a double iron source composite stage. Background Art

[0002] Lithium iron phosphate (LiFePO 4 ) is widely used in portable electronic devices and new energy vehicles due to its high safety, long cycle life, green and environmental protection, and low preparation cost. However, compared with ternary lithium, the energy density of lithium iron phosphate is not in an advantageous position. Therefore, on the material side, improving its compaction density has become one of the best ways to increase the energy density of lithium iron phosphate; at the same time, the traditional high-temperature solid-phase synthesis of lithium iron phosphate requires a carbon source for iron reduction. If lithium iron phosphate can be synthesized directly from the ferrous end, the cost can be further reduced. Summary of the invention

[0003] The purpose of the present invention is to improve the compaction density of lithium iron phosphate. The present invention controls the pH of the iron phosphate slurry section to prepare different iron sources, uses two paths to synthesize lithium iron phosphate in the same reaction vessel, and finally combines high and low temperature calcination to achieve the purpose of large and small particle grading. The method has a simple process flow, the synthetic material is green and environmentally friendly, and is easy to industrialize and develop.

[0004] The method for solving the problem in the present invention is achieved by the following technical solution: Step (1): adding ferrous sulfate and phosphoric acid into pure water and mixing thoroughly to obtain a solution, and then dividing the solution into solution A and solution B; Step (2): adding a dopant, an oxidant and phosphoric acid to solution A, and controlling the pH to be between 1 and 3 to obtain iron phosphate; Step (3): adding a dopant and ammonia water to solution B, and controlling the pH to be between 5 and 6 to obtain ferrous phosphate; Step (4): grinding and spraying the iron phosphate obtained in step (2) with a lithium source, a carbon source and pure water to obtain lithium iron phosphate yellow material A; grinding and spraying the ferrous phosphate obtained in step (3) with a lithium source, a carbon source and pure water to obtain lithium iron phosphate yellow material B; Step (5): placing lithium iron phosphate yellow material A in a furnace and calcining it to obtain precursor A, placing lithium ferrous phosphate yellow material B in a furnace and calcining it to obtain precursor B, and mixing precursors A and B in a certain mass ratio and calcining them to obtain a finished product.

[0005] The dopant in steps (2) and (3) is Mg 2+ 、Al 3+ 、Ti 4+ 、V 5+ 、Bi 3+A combination of one or more of them, where the dopants in steps (2) and (3) are the same or different.

[0006] The said Mg 2+ is selected from one or more of magnesium sulfate, magnesium chloride, magnesium carbonate, magnesium oxalate, magnesium acetate, and magnesium nitrate.

[0007] The said Al 3+ is selected from one or more of aluminum sulfate, aluminum chloride, aluminum carbonate, aluminum oxalate, aluminum acetate, and aluminum nitrate. The said Ti 4+ is selected from one or more of titanium oxysulfate, titanium dioxide, tetrabutyl titanate, and tetraethyl titanate.

[0008] The said V 5+ is selected from one or more of ammonium metavanadate, vanadium pentoxide, and vanadyl sulfate.

[0009] The said Bi 3+ is selected from one or more of bismuth sulfate and bismuth nitrate.

[0010] In step (2), the molar ratio of the metal ion in the dopant to Fe is 0.001 - 0.005:1, and the oxidant is one of hydrogen peroxide, oxygen, nitric acid, ammonium persulfate, and potassium permanganate; In step (3), the molar ratio of the dopant to Fe is 0.005 - 0.02:1.

[0011] Specifically, in step (4), the lithium source is one or more of lithium carbonate and lithium bicarbonate, and the carbon source is one or more of glucose, sucrose, fructose, and polyethylene glycol.

[0012] Specifically, in step (4), Fe 3+ :Li:C = 1:1 - 1.04:0.3 - 0.45, Fe 2+ :Li:C = 1:1 - 1.04:0.1 - 0.25, the solid content is controlled at 38 - 48%, the slurry particle size D50: 300 - 450 nm; the spray outlet air temperature is 75 - 85 °C.

[0013] Specifically, in step (5), the calcination temperature of yellow material A is 650 - 700 °C, and the heat preservation time is 6 - 8 h; the calcination temperature of yellow material B is 700 - 750 °C, and the heat preservation time is 6 - 8 h. The mixing ratio of precursor A and B is 4 - 2:6 - 8, the calcination temperature is 750 - 800 °C, and the heat preservation time is 4 - 6 h.

[0014] Compared with other lithium iron phosphate modification methods, the beneficial effects of the present invention are: By controlling the pH at the original slurry end of iron phosphate, two iron sources, iron phosphate and ferrous phosphate, are obtained. The experimental process is mature, the equipment compatibility is high, and the cost is low.

[0015] Two iron sources with different valence states are used, and two LFP precursors are synthesized by combining different formulation processes. Due to the different valence states of ferrous phosphate and iron phosphate, during the calcination process, due to the different rates of formation of LFP from ferrous and iron, as well as the different sintering temperatures and times, the final particle sizes are different, achieving the purpose of particle grading.

[0016] Doping at the iron source end avoids the interference of other raw materials at the back end on the doped elements, making it impossible to achieve the doping effect or causing loss of doped elements. At the same time, two different elements are doped into different iron sources respectively. Titanium can improve the intrinsic conductivity of the material, and vanadium can refine the particles and improve the rate performance. In the final lithium iron phosphate, the two doped elements produce effects independently, avoiding the problem of uneven doping caused by double doping. Brief Description of the Drawings

[0017] Figure 1 It is the scanning electron microscope image of Example 1.

[0018] Figure 2 It is the scanning electron microscope image of Comparative Example 1. Detailed Description of the Invention

[0019] The present invention will be further described in detail below in conjunction with the drawings and specific embodiments.

[0020] The present invention discloses a preparation method for synthesizing a high-compact lithium iron phosphate cathode material by using a dual-iron source composite grading. The following is a further elaboration of the inventive concept in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and not to limit the scope of the present invention. It should be understood that based on the content of the present invention, those skilled in the art make various modifications or alterations to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of this application.

[0021] Example 1 Purified ferrous sulfate and phosphoric acid are mixed to obtain the iron phosphate stock slurry, which is divided into two parts, A and B; Among them, the addition amount of ammonium metavanadate in A is fed according to the molar ratio of vanadium:iron = 0.001:1. Subsequently, hydrogen peroxide and phosphoric acid are added, and the pH is measured simultaneously. When the pH is 2.5, the precipitate is collected, filtered, washed, and dried to obtain iron phosphate; The addition amount of tetrabutyl titanate in B is fed according to the molar ratio of titanium:iron = 0.008:1. Subsequently, ammonia water is added, and the pH is measured simultaneously. When the pH is 5.6, the precipitate is collected, filtered, washed, and dried to obtain ferrous phosphate; Feed ferric phosphate, lithium carbonate, glucose, and PEG in a molar ratio of 1:1.01:0.3 (glucose and PEG are added as carbon sources in a molar ratio of 1:1, the same below), with a solid content of 38%, a sanding particle size D50 of 320 nm, and a spray drying outlet temperature of 75 °C to obtain yellow material A. Place yellow material A in a furnace, use nitrogen as the protective gas, with a calcination temperature of 650 °C and a heat preservation time of 6 h to obtain precursor A; Similarly, feed ferrous phosphate, lithium carbonate, glucose, and PEG in a molar ratio of 1:1.02:0.15, with a solid content of 39%, a sanding particle size D50 of 330 nm, and a spray drying outlet temperature of 76 °C to obtain yellow material B. Place yellow material B in a furnace, use nitrogen as the protective gas, with a calcination temperature of 700 °C and a heat preservation time of 7 h to obtain precursor B; Uniformly mix precursor A and B in a mass ratio of A:B = 4:6, place them in a furnace, use nitrogen as the protective gas, with a calcination temperature of 750 °C and a heat preservation time of 4 h to obtain the finished product LFP.

[0022] Example 2: Mix purified ferrous sulfate and phosphoric acid to obtain ferric phosphate slurry, and divide it into two parts, A and B; Among them, the addition amount of ammonium metavanadate in A is fed in a molar ratio of vanadium:iron = 0.003:1, then hydrogen peroxide and phosphoric acid are added, and the pH is measured simultaneously. When the pH is 1.3, collect the precipitate, filter, wash, and dry to obtain ferric phosphate; The addition amount of tetrabutyl titanate in B is fed in a molar ratio of titanium:iron = 0.01:1, then ammonia water is added, and the pH is measured simultaneously. When the pH is 5.4, collect the precipitate, filter, wash, and dry to obtain ferrous phosphate; Feed ferric phosphate, lithium carbonate, glucose, and PEG in a molar ratio of 1:1.02:0.2, with a solid content of 38%, a sanding particle size D50 of 340 nm, and a spray drying outlet temperature of 75 °C to obtain yellow material A. Place yellow material A in a furnace, use nitrogen as the protective gas, with a calcination temperature of 660 °C and a heat preservation time of 7 h to obtain precursor A; Similarly, feed ferrous phosphate, lithium carbonate, glucose, and PEG in a molar ratio of 1:1.01:0.2, with a solid content of 39%, a sanding particle size D50 of 330 nm, and a spray drying outlet temperature of 76 °C to obtain yellow material B. Place yellow material B in a furnace, use nitrogen as the protective gas, with a calcination temperature of 720 °C and a heat preservation time of 7 h to obtain precursor B; Uniformly mix precursor A and B in a mass ratio of A:B = 3:7, place them in a furnace, use nitrogen as the protective gas, with a calcination temperature of 770 °C and a heat preservation time of 4 h to obtain the finished product LFP.

[0023] Example 3: Mix the purified ferrous sulfate with phosphoric acid to obtain the raw slurry of iron phosphate, and divide it into two parts, A and B; Among them, the addition amount of ammonium metavanadate in A is fed according to the molar ratio of vanadium:iron = 0.005:1. Subsequently, hydrogen peroxide and phosphoric acid are added, and the pH is measured simultaneously. After the pH reaches 2.8, the precipitate is collected, filtered, washed, and dried to obtain iron phosphate; The addition amount of tetrabutyl titanate in B is fed according to the molar ratio of titanium:iron = 0.02:1. Subsequently, ammonia water is added, and the pH is measured simultaneously. After the pH is lower than 5.2, the precipitate is collected, filtered, washed, and dried to obtain ferrous phosphate; Feed iron phosphate, lithium carbonate, glucose, and PEG according to the molar ratio of 1:1.04:0.45. The solid content is 38%, the D50 of the sanding particle size is 400 nm, and the outlet temperature of spray drying is 75 °C to obtain yellow material A. Place yellow material A in a furnace, use nitrogen as the protective gas, the calcination temperature is 680 °C, and the heat preservation time is 8 h to obtain precursor A; Similarly, feed ferrous phosphate, lithium carbonate, glucose, and PEG according to the molar ratio of 1:1.04:0.25. The solid content is 39%, the D50 of the sanding particle size is 380 nm, and the outlet temperature of spray drying is 76 °C to obtain yellow material B. Place yellow material B in a furnace, use nitrogen as the protective gas, the calcination temperature is 720 °C, and the heat preservation time is 8 h to obtain precursor B; Uniformly mix precursor A and B according to the mass ratio of A:B = 2:8, place them in a furnace, use nitrogen as the protective gas, the calcination temperature is 800 °C, and the heat preservation time is 6 h to obtain the finished product LFP.

[0024] Comparative Example 1: Mix the purified ferrous sulfate with phosphoric acid to obtain the raw slurry of iron phosphate, and divide it into two parts, A and B; Among them, the addition amount of ammonium metavanadate in A is fed according to the molar ratio of vanadium:iron = 0.001:1. Subsequently, hydrogen peroxide and phosphoric acid are added, and the pH is measured simultaneously. After the pH reaches 2.3, the precipitate is collected, filtered, washed, and dried to obtain iron phosphate; The addition amount of tetrabutyl titanate in B is fed according to the molar ratio of titanium:iron = 0.008:1. Subsequently, ammonia water is added, and the pH is measured simultaneously. After the pH reaches 3.0, the precipitate is collected, filtered, washed, and dried to obtain iron phosphate; Feed iron phosphate, lithium carbonate, glucose, and PEG according to the molar ratio of 1:1.01:0.3. The solid content is 38%, the D50 of the sanding particle size is 320 nm, and the outlet temperature of spray drying is 75 °C to obtain yellow material A. Place yellow material A in a furnace, use nitrogen as the protective gas, the calcination temperature is 650 °C, and the heat preservation time is 6 h to obtain precursor A; Similarly, ferric phosphate, lithium carbonate, glucose, and PEG were fed in a molar ratio of 1:1.02:0.15, with a solid content of 39%, a sanding particle size D50 of 330 nm, and an air outlet temperature of 76 °C for spray drying to obtain yellow material B. The yellow material B was placed in a furnace, with nitrogen as the protective gas, a calcination temperature of 650 °C, and a heat preservation time of 7 h to obtain precursor B; Precursor A and B were uniformly mixed in a mass ratio of A:B = 4:6 and then placed in a furnace, with nitrogen as the protective gas, a calcination temperature of 750 °C, and a heat preservation time of 4 h to obtain the finished product LFP.

[0025] Comparative Example 2: Purified ferrous sulfate and phosphoric acid were mixed to obtain a ferric phosphate slurry, which was divided into two parts, A and B. In part A, ammonium metavanadate was added in a molar ratio of vanadium:iron = 0.003:1, and then hydrogen peroxide and phosphoric acid were added. At the same time, the pH was measured. After the pH reached 4.6, the precipitate was collected, filtered, washed, and dried to obtain ferric phosphate; In part B, tetrabutyl titanate was added in a molar ratio of titanium:iron = 0.01:1, and then ammonia water was added. At the same time, the pH was measured. After the pH reached 5.5, the precipitate was collected, filtered, washed, and dried to obtain ferrous phosphate.

[0026] Ferric phosphate, lithium carbonate, glucose, and PEG were fed in a molar ratio of 1:1.02:0.2, with a solid content of 38%, a sanding particle size D50 of 340 nm, and an air outlet temperature of 75 °C for spray drying to obtain yellow material A. The yellow material A was placed in a furnace, with nitrogen as the protective gas, a calcination temperature of 720 °C, and a heat preservation time of 7 h to obtain precursor A; Similarly, ferrous phosphate, lithium carbonate, glucose, and PEG were fed in a molar ratio of 1:1.01:0.2, with a solid content of 39%, a sanding particle size D50 of 330 nm, and an air outlet temperature of 76 °C for spray drying to obtain yellow material B. The yellow material B was placed in a furnace, with nitrogen as the protective gas, a calcination temperature of 720 °C, and a heat preservation time of 7 h to obtain precursor B; Precursor A and B were uniformly mixed in a mass ratio of A:B = 3:7 and then placed in a furnace, with nitrogen as the protective gas, a calcination temperature of 770 °C, and a heat preservation time of 4 h to obtain the finished product LFP.

[0027] Comparative Example 3: Purified ferrous sulfate and phosphoric acid were mixed to obtain a ferric phosphate slurry, which was divided into two parts, A and B. In part A, ammonium metavanadate was added in a molar ratio of vanadium:iron = 0.001:1, and then hydrogen peroxide and phosphoric acid were added. At the same time, the pH was measured. After the pH reached 2.2, the precipitate was collected, filtered, washed, and dried to obtain ferric phosphate; The addition amount of tetrabutyl titanate in B is fed according to the molar ratio of titanium:iron = 0.008:1, and then ammonia water is added. At the same time, the pH is measured. After the pH reaches 5.7, the precipitate is collected, filtered, washed and dried to obtain ferrous phosphate.

[0028] Ferric phosphate, lithium carbonate, glucose and PEG are fed according to the molar ratio of 1:1.01:0.3. The solid content is 38%, the D50 of the sand grinding particle size is 320 nm, and the outlet temperature of spray drying is 75 °C to obtain yellow material A. The yellow material A is placed in a furnace, nitrogen is used as the protective gas, the calcination temperature is 650 °C, and the heat preservation time is 6 h to obtain precursor A; Similarly, ferrous phosphate, lithium carbonate, glucose and PEG are fed according to the molar ratio of 1:1.02:0.15. The solid content is 39%, the D50 of the sand grinding particle size is 320 nm, and the outlet temperature of spray drying is 76 °C to obtain yellow material B. The yellow material B is placed in a furnace, nitrogen is used as the protective gas, the calcination temperature is 670 °C, and the heat preservation time is 7 h to obtain precursor B. Precursor A and B are uniformly mixed according to the mass ratio of A:B = 1:9 and then placed in a furnace. Nitrogen is used as the protective gas, the calcination temperature is 750 °C, and the heat preservation time is 4 h to obtain the finished product LFP.

[0029] Comparative Example 4: Purified ferrous sulfate and phosphoric acid are mixed to obtain ferric phosphate stock solution, which is divided into two parts, A and B. Among them, the addition amount of ammonium metavanadate in A is fed according to the molar ratio of vanadium:iron = 0.003:1, and then hydrogen peroxide and phosphoric acid are added. At the same time, the pH is measured. After the pH is lower than 3, the precipitate is collected, filtered, washed and dried to obtain ferric phosphate; The addition amount of tetrabutyl titanate in B is fed according to the molar ratio of titanium:iron = 0.01:1, and then ammonia water is added. At the same time, the pH is measured. After the pH is lower than 6, the precipitate is collected, filtered, washed and dried to obtain ferrous phosphate.

[0030] Ferric phosphate, lithium carbonate, glucose and PEG are fed according to the molar ratio of 1:1.02:0.2. The solid content is 38%, the D50 of the sand grinding particle size is 400 nm, and the outlet temperature of spray drying is 75 °C to obtain yellow material A. The yellow material A is placed in a furnace, nitrogen is used as the protective gas, the calcination temperature is 620 °C, and the heat preservation time is 5 h to obtain precursor A; Similarly, ferrous phosphate, lithium carbonate, glucose and PEG are fed according to the molar ratio of 1:1.01:0.2. The solid content is 39%, the D50 of the sand grinding particle size is 400 nm, and the outlet temperature of spray drying is 76 °C to obtain yellow material B. The yellow material B is placed in a furnace, nitrogen is used as the protective gas, the calcination temperature is 650 °C, and the heat preservation time is 9 h to obtain precursor B; Precursor A and B are uniformly mixed in a mass ratio of A:B = 3:7 and then placed in a furnace. Using nitrogen as the protective gas, the calcination temperature is 770 °C, and the heat preservation time is 4 h to obtain the finished product LFP.

[0031] Comparative Example 5: Purified ferrous sulfate and phosphoric acid are mixed to obtain the crude iron phosphate slurry, which is divided into two parts, A and B. Among them, the addition amount of ammonium metavanadate in A is fed according to a molar ratio of vanadium:iron = 0.005:1. Subsequently, hydrogen peroxide and phosphoric acid are added, and the pH is measured simultaneously. When the pH is lower than 3, the precipitate is collected, filtered, washed, and dried to obtain iron phosphate. The addition amount of tetrabutyl titanate in B is fed according to a molar ratio of titanium:iron = 0.02:1. Subsequently, ammonia water is added, and the pH is measured simultaneously. When the pH is lower than 6, the precipitate is collected, filtered, washed, and dried to obtain ferrous phosphate.

[0032] Iron phosphate, lithium carbonate, glucose, and PEG are fed according to a molar ratio of 1:1.04:0.45. The solid content is 38%, the sanding particle size D50 is 400 nm, and the outlet temperature of spray drying is 75 °C to obtain yellow material A. Yellow material A is placed in a furnace. Using nitrogen as the protective gas, the calcination temperature is 720 °C, and the heat preservation time is 8 h to obtain precursor A. Similarly, ferrous phosphate, lithium carbonate, glucose, and PEG are fed according to a molar ratio of 1:1.04:0.25. The solid content is 39%, the sanding particle size D50 is 380 nm, and the outlet temperature of spray drying is 76 °C to obtain yellow material B. Yellow material B is placed in a furnace. Using nitrogen as the protective gas, the calcination temperature is 780 °C, and the heat preservation time is 6 h to obtain precursor B. Precursor A and B are uniformly mixed in a mass ratio of A:B = 2:8 and then placed in a furnace. Using nitrogen as the protective gas, the calcination temperature is 720 °C, and the heat preservation time is 7 h to obtain the finished product LFP.

[0033] Table 1: Parameter changes and result comparison of examples and comparative examples

[0034] Electrical property test method The materials of each example and comparative example were respectively mixed with a conductive agent (Super P) and a PVDF solution dissolved in NMP in a ratio of 90:5:5, then coated on a carbon-coated aluminum foil, vacuum dried at 110 °C, and pressed into a disc with a diameter of 12 mm as the positive electrode, a metallic lithium sheet as the negative electrode, a Celgard 2300 microporous membrane as the separator, and a solution of 1.0 mol / L LiPF6 in ethylene carbonate (EC):dimethyl carbonate (DMC) = 1:1 as the electrolyte. An R2025 button cell was assembled in a glove box and left to stand at room temperature (25 °C) for 8 h, and then a Neware 3008 battery test system was used for room temperature testing: first charged to 3.75 V at 0.1 C, discharged to 2 V at 0.1 C; after standing for 5 min, continued charging at 0.1 C and discharging at 3 C to 2 V, and the discharge specific capacities at 0.1 C and 3 C were recorded.

[0035] Similarly, after standing at room temperature (25 °C) for 8 h, a Neware 3008 battery test system was used for high temperature testing at 45 °C: first charged to 3.75 V at 0.1 C, discharged to 2 V at 0.1 C, and cycled 3 times. Subsequently, first charged to 3.75 V at 0.1 C, placed in a 45 °C constant temperature oven and left to stand for 5 min, and then discharged at 0.5 C, and the discharge specific capacity was recorded. The calculation method of the 0.5 C plateau specific capacity: during 0.5 C discharge, the capacity with a discharge voltage above 3.2 V / the total 0.5 C discharge capacity.

[0036] 1. Table 1 shows the parameter changes and result comparisons between the examples and the comparative examples. The tap densities of the three examples all exceeded 2.6 g / cm 3 , at room temperature, both 0.1 C and 3 C maintained extremely high discharge specific capacities. At the same time, in a high temperature environment of 45 °C, the 0.5 C plateau retention rates were all higher than 97%. The plateau retention rate reflects the polarization degree of lithium iron phosphate. The higher the plateau retention rate, the smaller the polarization degree of lithium iron phosphate. The above data show that within the optimal formulation range, the materials can achieve excellent comprehensive performance. For the five comparative examples, the types of mixed iron sources, the mixing mass ratio of iron sources, the calcination temperatures of the two iron sources, and the sintering temperature of the mixed iron sources were respectively changed. It can be found that after mixing with a single iron source, when the two batches of materials were calcined, the large and small particles tended to be consistent, resulting in a low tap density; after the mixing mass ratio of the iron sources changed, the large and small particles were not in the best grading state, so the tap density could not be improved; similarly, after the calcination temperatures of the two iron sources changed, the particle size, crystallinity, and carbon content of the materials all changed, and finally they could not reach a high tap density state after mixing; finally, the sintering temperature of the mixed iron source could affect the carbon content and secondary growth state of the mixed material, and the tap density would also decrease after the change.

[0037] 2. When mixing the two iron sources, during calcination, due to different iron valence states, Fe 3+It needs to be reduced by carbon obtained from the decomposition of organic carbon sources to obtain Fe 2+ , and then participate in the synthesis of lithium iron phosphate; while Fe 2+ can directly carry out the synthesis of lithium iron phosphate. The reaction steps of the two iron sources are different, resulting in different particle growth rates. The growth rate of Fe 3+ is slow, the particles are small, and at the same time the calcination temperature is low and the carbon content is high, which can improve the electrical performance; the growth rate of Fe 2+ is fast, the particles are large, and at the same time the calcination temperature is relatively high and the carbon content is low, which can improve the compaction. Finally, two different states of precursors are obtained. After mixing in a certain proportion and then calcining, a material with excellent compaction density and electrical performance is obtained.

[0038] 3. Through the comprehensive performance of a preparation method for synthesizing high-compaction lithium iron phosphate cathode materials using a dual-iron-source composite grading in specific examples, it can be found that the present invention can simultaneously improve the electrical performance and compaction density of the material; in addition, the lithium iron phosphates obtained by the preparation method provided by the present invention under different combinations of lithium sources, iron sources, phosphorus sources, and vanadium sources all have good electrochemical performance, indicating that the preparation method has good universality and is conducive to large-scale use.

Claims

1. A method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite level, characterized in that: The following steps are involved: Step (1): adding ferrous sulfate and phosphoric acid into pure water and mixing thoroughly to obtain a solution, and then dividing the solution into solution A and solution B; Step (2): adding a dopant, an oxidant and phosphoric acid to solution A, and controlling the pH to be between 1 and 3 to obtain iron phosphate; Step (3): adding a dopant and ammonia water to solution B, and controlling the pH to be between 5 and 6 to obtain ferrous phosphate; Step (4): grinding and spraying the iron phosphate obtained in step (2) with a lithium source, a carbon source and pure water to obtain lithium iron phosphate yellow material A; grinding and spraying the ferrous phosphate obtained in step (3) with a lithium source, a carbon source and pure water to obtain lithium iron phosphate yellow material B; Step (5): placing lithium iron phosphate yellow material A in a furnace and calcining it to obtain precursor A, placing lithium ferrous phosphate yellow material B in a furnace and calcining it to obtain precursor B, and mixing precursors A and B in a certain mass ratio and calcining them to obtain a finished product.

2. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: The dopant in steps (2) and (3) is Mg 2+ 、Al 3+ 、Ti 4+ 、V 5+ 、Bi 3+ A combination of one or more of the foregoing, wherein the dopants in steps (2) and (3) are the same or different.

3. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: Step (2) The molar ratio of metal ions to Fe in the dopant is 0.001-0.005:1, and the oxidant is one of hydrogen peroxide, oxygen, nitric acid, ammonium persulfate and potassium permanganate; In step (3), the molar ratio of the dopant to Fe is 0.005-0.02:

1.

4. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: In step (4), the lithium source is one or more of lithium carbonate and lithium bicarbonate, and the carbon source is one or more of glucose, sucrose, fructose, and polyethylene glycol.

5. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: Step (4) Preparation of lithium iron phosphate yellow material A, Fe in iron phosphate 3+ The molar ratio of Li in the lithium source and the carbon source C is 1:1-1.04:0.3-0.

45.

6. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: Preparation of lithium iron phosphate yellow material B, Fe in ferrous phosphate 2+ The molar ratio of Li in the lithium source and the carbon source C is 1:1-1.04:0.1-0.25, the solid content is controlled at 38-48%, and the slurry particle size D50: 300-450nm.

7. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: In step (5), the calcination temperature of lithium iron phosphate yellow material A is 650-700° C., and the holding time is 6-8 h.

8. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: In step (5), the calcination temperature of the lithium iron phosphate yellow material B is 700-750° C., and the holding time is 6-8 hours.

9. The method for preparing a high-density lithium iron phosphate positive electrode material using a dual iron source composite stage according to claim 1, characterized in that: The mixing ratio of precursor A and B is 4-2:6-8, the calcination temperature is 750-800°C, and the insulation time is 4-6h.

10. The double iron source composite level is combined into a high-density lithium iron phosphate positive electrode material, characterized in that: Prepared by any method of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of high-performance lithium ion battery positive material lithium iron phosphate

    CN107381529A

  • Method to manufacture activate substance for positive electrode and method of manufacturing non aqueous electrolyte cell

    JP2001250555A

  • Method for preparing carbon-coated lithium iron phosphate material from ferrous phosphate

    US20230080632A1

  • High-tap-density lithium iron phosphate positive electrode material, and preparation method therefor and use thereof

    WO2023226372A1

  • Preparation method for and use of iron phosphate material

    WO2025015831A1

Cited By

  • A lithium iron phosphate cathode material with high rate and high compaction performance and a preparation method thereof

    CN122685037A